A kegyes élet heti ritmusa – A nyugalom napjának keresztyén sajátosságai - SIBA, Balázs (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
Weekly Rhythm of Gracious Life – Christian Features of the Seventh Day. This study reflects on that “many Christians and others now keep a weekend of two Saturdays.” Our consumer culture has made the seventh day not a holy day, but a kind of extra time to catch up with the tasks of everyday rush. The seventh day is not only necessary because of our biological and sociological needs, but it also has a theological dimension. Sacred time can take many forms, and we are not bound by time and space to pray to God, but the Sunday is a great opportunity to come together to experience the miracle of God’s presence in our community. In this article, we look at the four elements to a holy day: rest, remember, give thanks, and refocus.